2014
DOI: 10.1002/14651858.cd008420.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial keratoplasty versus penetrating keratoplasty for Fuchs endothelial dystrophy

Abstract: Background-Fuchs endothelial dystrophy (FED) is a condition in which there is premature degeneration of corneal endothelial cells. When the number of endothelial cells is reduced to a significant degree, fluid begins to accumulate within the cornea. As a result, the cornea loses its transparency and the individual suffers a reduction in vision. The only successful surgical treatment for this condition is replacement of part or all of the cornea with healthy tissue from a donor. The established procedure, penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 66 publications
(64 reference statements)
1
70
0
10
Order By: Relevance
“…The two groups, however, had different treatment regimens and were from different centres; that is all the patients who had PK were from the Swedish Corneal Transplant Registry. Nanavaty et al in their Cochrane Review (8) , noted that for Fuchs' endothelial dystrophy (FED), EK was associated with a lower rejection rate (2-4%) compared to PK (5.3-23.2%), although the mean follow-up was considerably longer for the PK than the EK group. In contrast, Lee et al (9) reviewed 34 peer-reviewed articles and concluded that the mean rejection rate following EK was 10% and was similar to that following PK, but with a high variation of between 0% and 45.5%.…”
Section: Introductionmentioning
confidence: 99%
“…The two groups, however, had different treatment regimens and were from different centres; that is all the patients who had PK were from the Swedish Corneal Transplant Registry. Nanavaty et al in their Cochrane Review (8) , noted that for Fuchs' endothelial dystrophy (FED), EK was associated with a lower rejection rate (2-4%) compared to PK (5.3-23.2%), although the mean follow-up was considerably longer for the PK than the EK group. In contrast, Lee et al (9) reviewed 34 peer-reviewed articles and concluded that the mean rejection rate following EK was 10% and was similar to that following PK, but with a high variation of between 0% and 45.5%.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Despite these advantages, most studies have suggested that graft survival between PK and EK are actually similar (though few have been direct comparative studies). 9 Nonetheless, after a failed primary PK, a surgeon may now choose to selectively replace the endothelium by performing an EK under the existing PK, instead of the traditional repeat PK, which has been shown to have poor long-term survival rates of 21%-70%. [10][11][12][13][14][15][16][17][18] As EK has been shown to potentially have a lower rejection risk compared to PK, one advantage of performing EK over PK would be the potential for a reduced risk of rejection, as compared to a repeat PK.…”
mentioning
confidence: 99%
“…Beaucoup d'études rapportent des pertes cellulaires endothéliales après DSEK comparables à celles observées après kératoplastie transfixiante, allant de 15 % à 61 % à 1 an [9][10][11][12][13][14][15]. D'autres études rapportent une perte cellulaire endothéliale plus importante après DSEK qu'après kérato-plastie transfixiante [2,16,17]. Il est très probable que cette deuxième hypothèse soit exacte car la découpe du greffon au microkératome et son insertion dans la chambre antérieure induisent une perte cellulaire endothéliale additionnelle par rapport à la kératoplastie transfixiante [2].…”
Section: Discussionunclassified